2022
DOI: 10.3389/fpubh.2022.955008
|View full text |Cite
|
Sign up to set email alerts
|

Three leading suicide methods in the United States, 2017–2019: Associations with decedents' demographic and clinical characteristics

Abstract: Background and aimsThe U.S. suicide data show that use of lethal methods, specifically firearms and hanging/suffocation, has been increasing among young and middle-aged adults of both sexes over the past decades. In this study, we examined demographic and clinical correlates of use of firearms, hanging/suffocation, and poisoning as suicide methods among suicide decedents age 18+.MethodsData came from the 2017-2019 National Violent Death Reporting System (NVDRS; N = 94,454, age ≥ 18 at the time of suicide; 74,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“… 2 When meta-analyses examined the association between a given risk factor and multiple suicide-related outcomes (commonly ideation, attempt, and death), we only included the data specifically relating to suicide mortality (although in a secondary analysis, we compared effect sizes for these different outcomes when reported in the same meta-analysis). Reviews that solely focused on suicide deaths by a specific method (eg, hanging, poisoning, or firearms) were excluded because these are differentially associated with specific demographic and clinical factors, 11 , 12 which would limit generalisability (eg, compared with other methods, people who die by firearms are less likely to have a history of suicide attempts or mental illness).…”
Section: Methodsmentioning
confidence: 99%
“… 2 When meta-analyses examined the association between a given risk factor and multiple suicide-related outcomes (commonly ideation, attempt, and death), we only included the data specifically relating to suicide mortality (although in a secondary analysis, we compared effect sizes for these different outcomes when reported in the same meta-analysis). Reviews that solely focused on suicide deaths by a specific method (eg, hanging, poisoning, or firearms) were excluded because these are differentially associated with specific demographic and clinical factors, 11 , 12 which would limit generalisability (eg, compared with other methods, people who die by firearms are less likely to have a history of suicide attempts or mental illness).…”
Section: Methodsmentioning
confidence: 99%
“…been attributed to the fact that they engage in suicidal behaviors with greater premeditation, lethality of intent, and lethality of method, firearms in particular, than do younger adults (4,5). While firearms are the most and second most frequently used suicide method among all adult males and females, respectively, in the US, older adults are far more likely to use firearms than younger adults (6)(7)(8)(9). A study of suicide decedents in the 2017-2019 National Violent Death Reporting System (NVDRS) showed that firearms were used in 55 and 30% of all adult male and female suicides, respectively, but they were used in 75 and 34% of male and female suicides, respectively, in the 65+ age group (6).…”
Section: Introductionmentioning
confidence: 99%
“…While firearms are the most and second most frequently used suicide method among all adult males and females, respectively, in the US, older adults are far more likely to use firearms than younger adults (6)(7)(8)(9). A study of suicide decedents in the 2017-2019 National Violent Death Reporting System (NVDRS) showed that firearms were used in 55 and 30% of all adult male and female suicides, respectively, but they were used in 75 and 34% of male and female suicides, respectively, in the 65+ age group (6). Among older male suicide decedents, 70.2, 88.8, and 80.3% of those age 65-74, 75-84, and 85+, respectively, used firearms (6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations